Beneficial properties of natural phenols: Highlight on protection against pathological conditions associated with amyloid aggregation. (3rd June 2014) - Stefani, Massimo; Rigacci, Stefania
Abstract Mediterranean and Asian diets are currently considered as the most healthy traditional feeding habits effective against risk of age‐associated, particularly cardiovascular and neurodegenerative, diseases. A common feature of these two regimens is the abundance of foods and beverages of plant origin (green tea, extra virgin olive oil, red wine, spices, berries, and aromatic herbs) that are considered responsible for the observed beneficial effects. Epidemiological data suggest that the phenolic component remarkably enriched in these foods plays an important role in reducing the incidence of amyloid diseases, pathological conditions associated to tissue deposition of toxic protein aggregates responsible for progressive functional deterioration. Great effort is being spent to provide knowledge on the effects of several natural phenols in this context, moving from the test tube to animal models and, more slowly, to the patient's bed. An emerging feature that makes these molecules increasingly attractive for amyloid disease prevention and therapy is their wide spectrum of activity: recent pieces of evidence suggest that they can inhibit the production of amyloidogenic peptides from precursors, increase antioxidant enzyme activity, activate autophagy and reduce inflammation. Our concept should than shift from considering natural phenols simply as antioxidants or, at the best, as amyloid aggregation inhibitors, to describing them as potentially multitargeting drugs. A main concern is the low bioavailability of such compounds and efforts aimed at improving it are underway, with encapsulation strategies being the most promising ones. © 2014 BioFactors, 40(5):482–493, 2014